2023
DOI: 10.1021/acscatal.3c02997
|View full text |Cite
|
Sign up to set email alerts
|

A Designed Chemoenzymatic Route for Efficient Synthesis of 6-Dehydronandrolone Acetate: A Key Precursor in the Synthesis of C7-Functionalized Steroidal Drugs

Zili Zhang,
Chenghua Gao,
Jing Zhao
et al.

Abstract: Dehydronandrolone acetate (3) is a crucial precursor for the synthesis of C7-functionalized steroidal drugs. However, the current production method involves a laborious and environmentally unfriendly five-step chemical process, resulting in a low efficiency. To overcome this, we report a chemoenzymatic strategy, involving a one-pot biocatalytic C7β-hydroxylation/C17β-ketoreduction of 19-norandrostenedione (1) by combination of P450 monooxygenase and 17-ketosteroid reductase to generate C7β-hydroxynandrolone (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…A new chemoenzymatic pathway, where 52 undergoes a one‐pot biocatalytic C7β‐hydroxylation/17β‐ketoreduction to produce C7β‐hydroxynandrolone ( 53 ). Subsequently, a one‐pot chemical dehydration and esterification process leads to the formation of 54 with an impressive overall yield of 93 % (Scheme 8C) [31] . These findings highlight the potential of protein engineering in overcoming the challenges associated with synthetic requirements and the properties of native enzyme catalysts.…”
Section: Enzyme Cascade In Chemoenzymatic Synthesis Of Steroidsmentioning
confidence: 83%
See 2 more Smart Citations
“…A new chemoenzymatic pathway, where 52 undergoes a one‐pot biocatalytic C7β‐hydroxylation/17β‐ketoreduction to produce C7β‐hydroxynandrolone ( 53 ). Subsequently, a one‐pot chemical dehydration and esterification process leads to the formation of 54 with an impressive overall yield of 93 % (Scheme 8C) [31] . These findings highlight the potential of protein engineering in overcoming the challenges associated with synthetic requirements and the properties of native enzyme catalysts.…”
Section: Enzyme Cascade In Chemoenzymatic Synthesis Of Steroidsmentioning
confidence: 83%
“…Subsequently, a one-pot chemical dehydration and esterification process leads to the formation of 54 with an impressive overall yield of 93 % (Scheme 8C). [31] These findings highlight the potential of protein engineering in overcoming the challenges associated with synthetic requirements and the properties of native enzyme catalysts. Furthermore, the successful gram-scale synthesis of steroids demonstrates the practical applications of this chemoenzymatic route.…”
Section: Enzyme Cascade In Chemoenzymatic Synthesis Of Steroidsmentioning
confidence: 92%
See 1 more Smart Citation
“…VD-BM3, featuring an engineered substrate access channel, has demonstrated a high efficiency in the hydroxylation conversion rate of PG but with poor regioselectivity. An effective strategy to enhance regioselectivity is to rationally engineer residues near the substrate to bring the catalytic group of the substrate closer to the enzyme’s active site. ,, The docking results of PG and VD-BM3 complexes revealed that S72 and L437 were located within a 4-Å range of the AB ring of PG and hence were selected for saturation mutagenesis to recalibrate the distances of the D ring of PG toward the heme center (Figure A, B). S72Q -VD-BM3 was capable of producing 97% a at an 80% conversion rate (Table ), while S72H-VD-BM3 produced 97% d at a 30% conversion rate.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al have developed a chemoenzymatic route for the synthesis of 6-dehydronandrolone acetate, a common precursor of these steroids. [9] Chemo-enzymatic synthesis is a combination of biosynthesis and chemosynthesis, which has complementary and synergistic advantages in the synthesis of bioactive compounds. In this review, we summarize the recent advances in chemo-enzymatic synthesis of bioactive compounds derived from TCM and medicinal plants, put forward our perspective of chemo-enzymatic approach for the synthesis of promising bioactive compounds.…”
Section: Introductionmentioning
confidence: 99%